Immunohistochemical and morphometric study of pituitary pars distalis thyrotrophs of male viscacha (Lagostomus maximus maximus): seasonal variations and effect of melatonin and castration - Filippa, Veronica Palmira (2008)
The physiology and behavior of viscacha vary along the year according to the modifications of environmental signals such as the photoperiod length, temperature, rainfall pattern, food composition, and social interactions. The pituitary pars distalis thyrotrophs (TSH cells) of male viscacha were immunohistochemically identified, and the morphometric parameters: percentage of immunopositive area (% IA), cell percentage in pars distalis (% PDC), number of cells per reference area (no. cells/RA), and major cellular and nuclear diameters were analyzed. Three different groups of adult male viscachas were used: (1) captured in their natural habitat during the year, (2) melatonin-administered, and (3) castrated. The thyrotrophs were localized in the ventromedial sector, mainly in the pars distalis cephalic extreme. They were oval or pyramidal in shape, and their immunostaining intensity was heterogeneous. The % IA, % PDC, and no. cells/RA exhibited a significant decrease in June–July (winter, gonadal regression period) in relation to February–March (summer–early autumn, reproductive period), and they were recovered in August–September (later winter–early spring, gonadal recovery period). No morphometric variations of TSH cells were observed in melatonin-treated animals, whereas a decrease of the % IA, % PDC, and no. cells/RA was observed in castrated animals in relation to the intact animals. Our results show TSH cell morphometric variations during the year in agreement with the animal’s different physiological conditions during the reproductive cycle, and probably in response to the environmental signals changes. Melatonin does not have a direct effect on the TSH cells. However, castration modifies some thyrotroph morphometric parameters, reinforcing the hypothesis that androgens affect the cells activity.